What determines which children work? Empirical evidence from Kenya - Elin Vimefall (Örebro University School of Business, 2011)
This paper determines which children work and how much children work in Kenya. The results show that the educational level of the head of household is important, but it does not matter if the head has primary or higher education. Social norms have a strong effect on the child's probability of working and access to the labor market is important. The overall finding is not consistent with the view that it is children from the poorest families who work.
Keywords: D19; J22; J81; O12; 330; Child labor; Education; Kenya